Room-Temperature Assembled MXene-Based Aerogels for High Mass-Loading Sodium-Ion Storage - Song, Fei; Hu, Jian; Li, Guohao; Wang, Jie; Chen, Shuijiao; Xie, Xiuqiang; Wu, Zhenjun; Zhang, Nan (Nano-Micro Letters, 2021)
Low-temperature assembly of MXene nanosheets into three-dimensional (3D) robust aerogels addresses the crucial stability concern of the nano-building blocks during the fabrication process, which is of key importance for transforming the fascinating properties at the nanoscale into the macroscopic scale for practical applications. Herein, suitable cross-linking agents (amino-propyltriethoxysilane, Mn2+, Fe2+, Zn2+, and Co2+) as interfacial mediators to engineer the interlayer interactions are reported to realize the graphene oxide (GO)-assisted assembly of Ti3C2Tx MXene aerogel at room temperature. This elaborate aerogel construction not only suppresses the oxidation degradation of Ti3C2Tx but also generates porous aerogels with a high Ti3C2Tx content (87 wt%) and robustness, thereby guaranteeing the functional accessibility of Ti3C2Tx nanosheets and operational reliability as integrated functional materials. In combination with a further sulfur modification, the Ti3C2Tx aerogel electrode shows promising electrochemical performances as the freestanding anode for sodium-ion storage. Even at an ultrahigh loading mass of 12.3 mg cm−2, a pronounced areal capacity of 1.26 mAh cm−2 at a current density of 0.1 A g−1 has been achieved, which is of practical significance. This work conceptually suggests a new way to exert the utmost surface functionalities of MXenes in 3D monolithic form and can be an inspiring scaffold to promote the application of MXenes in different areas. Highlights: 1 Room temperature graphene oxide-assisted assembly of 3D Ti3C2Tx MXene aerogels have been realized by introducing interfacial mediators (amino-propyltriethoxysilane, Mn2+, Fe2+, Zn2+, and Co2+). 2 The methodology not only suppresses the oxidation degradation of Ti3C2Tx, but also generates porous aerogels with a high Ti3C2Tx content (87 wt%) and robustness. 3 As freestanding electrode of the as-prepared Ti3C2Tx-based aerogel with a practical-level mass loading of 12.3 mg cm-2 still delivers an areal capacity of 1.26 mAh cm-2 at a current density of 0.1 A g-1.